ANALISIS ALTERNATIF PILIHAN INVESTASI PADA ERA DIGITALISASI - Meitta Adiyono; Rossje V. Suryaputri; Efan Efan; Hendy Kumala (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2021)
The purpose of this study is to determine and analyze the performance comparison of stocks, cryptocurrencies and gold that can be used as an alternative investment in the era of digitalization. The population in this study is the monthly closing price of LQ45 shares, JKII shares, bitcoin and gold from January 2015 - December 2020, which is 72 datas in each comparison. The sampling technique of this research is saturated samples. The analytical method used is the comparative method and the data used are secondary data. Data is calculated using the Microsoft Excel program based on the formula of each variable. The data was processed statistically using the SPSS application, the Kruskall-Wallis Test. The results of this study indicate that there are significant differences between LQ45 stocks, Syariah stocks, bitcoin, and gold when measured from risk, sharpe performance’s measure, and treynor’s performance’s measure. Then, there are no significant difference between LQ45 stocks, Syariah stocks, bitcoin, and gold when measured from return and jensen's performance measure.